The impact of the COVID‐19 pandemic on hospitalizations for oral and oropharyngeal cancer in Brazil - da Cunha, Amanda Ramos (Community Dent Oral Epidemiol, 2021)
Timely diagnosis and treatment of oral and oropharyngeal cancers are central for the patient's survival. Our objective was to document the impact of the COVID‐19 pandemic on the rate of hospitalizations due to these cancers in Brazil's National Health System (SUS). The number of hospitalizations by these cancers during the first periods of the pandemic—and between the same period of 2016 to 2019—was retrieved from the SUS Hospital Information System. We compared hospitalization rates between pre‐ and pandemic periods, by State. The hospitalization rate for oral and oropharyngeal cancer during the pandemic was lower than that of the same period of previous years. The decline between 2019 and 2020 was of 49.3%, reaching 60% in the North. The reduction in hospitalization during an extended period suggests that oral and oropharyngeal cancer care will be postponed, with potentially detrimental impact on survival.